2020
DOI: 10.15763/issn.2376-5267.2019.1.6.47-81
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Team While Travelling: Infusing Elements of High Impact Practices into a Study Abroad Course for Student-Athletes

Abstract: Undergraduate institutions today are increasingly looking to adopt high impact practices (HIP) as a means to provide optimal learning experiences for their students. Study abroad courses are a particularly popular HIP offerings for students, as they provide opportunities to not only experience new cultures around the world but also to gain insights into their own cultural identities. However, because of the many demands placed on Division I collegiate student-athletes, they unfortunately are often not able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In considering ways to increase access and participation for intercollegiate student-athletes in HIPs it may be important for universities to do an internal assessment of the HIPs that their studentathletes are participating in and the barriers that they are encountering (Hall, Ketcham, & Weaver, 2018;Ishaq & Bass, 2019). Additionally, universities are and should continue to consider creative ways to increase access and participation through shorter term global experiences, utilizing summer for experiences that might not be possible during the academic year (e.g., global engagement and undergraduate research), and increasing academic partnerships with on-campus resources around service learning and internships (Buckmaster et al, 2019;Hall et al, 2020;Hall, Ketcham, & Weaver, 2018;Leupold, Weaver & Hall, 2019;Weaver et al, 2019;Williams et al, 2019). Finally, education around the benefits of HIPs for intercollegiate student-athletes should be conveyed to coaches and athletic administrators to demonstrate the importance of these experiences.…”
Section: Discussion Of Phases 1-3 Intercollegiate Athletic Performanc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In considering ways to increase access and participation for intercollegiate student-athletes in HIPs it may be important for universities to do an internal assessment of the HIPs that their studentathletes are participating in and the barriers that they are encountering (Hall, Ketcham, & Weaver, 2018;Ishaq & Bass, 2019). Additionally, universities are and should continue to consider creative ways to increase access and participation through shorter term global experiences, utilizing summer for experiences that might not be possible during the academic year (e.g., global engagement and undergraduate research), and increasing academic partnerships with on-campus resources around service learning and internships (Buckmaster et al, 2019;Hall et al, 2020;Hall, Ketcham, & Weaver, 2018;Leupold, Weaver & Hall, 2019;Weaver et al, 2019;Williams et al, 2019). Finally, education around the benefits of HIPs for intercollegiate student-athletes should be conveyed to coaches and athletic administrators to demonstrate the importance of these experiences.…”
Section: Discussion Of Phases 1-3 Intercollegiate Athletic Performanc...mentioning
confidence: 99%
“…This can be accomplished by creating paths to access by assessing current experiences and intentionally deepening them to meet the quality elements of HIPs. In addition to the significant work that has been ongoing on ways to implement strategies to increase intercollegiate athlete access and participation in the traditional HIPs, (Buckmaster et al, 2019;Hall et al, 2020;Hall, Ketcham, & Weaver, 2018;Ishaq & Bass, 2019;Leupold, Weaver & Hall, 2019;Weaver et al, 2019;Williams et al, 2019). In recent years, it has been suggested that the list of HIPs expand beyond academic experiences to a 'nextgeneration' list including co-curricular experiences such as student employment and college athletics; experiences that reach a significant level of immersion (Kuh et al, 2017;Kuh & O'Donnell, 2013).…”
mentioning
confidence: 99%